Mejora en el proceso de producción de suelas de poliuretano en la empresa Pionnisan S.A.C. - Rodriguez Saes, Alison Camila (2020)
The present study, carried out at the company Pionnisan SAC, proposes an improvement in the production process of polyurethane soles, in order to increase customer satisfaction and reduce extra costs generated by excess waste and defective products. Firstly, the relevant aspects of the company were identified, Pionnisan is dedicated to the manufacture of footwear soles, its principle costumer is the female segment. The increase in demand, the market growth and the constant competition force the company to make its processes more efficient. Secondly, the current situation of the key processes, indicators and improvement opportunities that directly impact profitability were analyzed. Through the diagnostic, a specific area was selected. In this case, the production of polyurethane soles was determined as the object of study because it generates a greater economic contribution to the company. The indicators of this area were analyzed in order to find the causes of the main problems. Thirdly, the possible solution alternatives were determined according to each cause and then, the best and primary solution was selected according to the quantitative and qualitative evaluation criteria. Fourthly, the solution, which was the creation of a quality control process, was developed and it involved the creation of a standard work procedure and a quality control process making use of the sampling technique. Finally, the financial evaluation of the improvement proposal is shown, whose Net Present Value (NPV) and Internal Ratio of Return (IRR) indicators show its viability. An NPV of 99 318 soles and an IRR of 66 % were obtained. In addition, in the worst-case scenario, a positive NPV of 792 soles and an IRR of 2,34% were obtained, which indicates that even in this case, the proposed solution continues to be beneficial for the company.